Technical-economic evaluation of bacterial consortia in strawberry cultivation across two production systems - Flórez-Hernández, Erika Alexandra; Montes-Ciro, Erika; Hurtado Salazar, Alejandro; Aristizábal, Juan Carlos; Ceballos-Aguirre, Nelson (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
Strawberry production is predominantly carried out in open fields, rendering it vulnerable to pest attacks, which can lead to reductions in yield. This susceptibility is further exacerbated by adverse climatic conditions. Another challenge is the high cost of inputs like fertilizers. Consequently, the aim of this study was to evaluate both technically and economically the impact of applying bacterial bio-fertilizers to strawberry crops under two production systems. The experimental design employed was a subdivided-plot arrangement in a randomized complete block, with the main plot focusing on the production system (either open field or macrotunnel), the subplot on plastic mulch (either with or without), and the sub-subplot on bacterial consortia treatments commercial. These were as follows: (a) control, which corresponded to traditional farmer management; (b) Bacillus subtilis, (c) consortium 1, comprising a mixture of humic acids and Rhodopseudomonas palustris, Bacillus subtilis, Bacillus amyloliquefaciens, Bacillus licheniformis; and (d) consortium 2, composed of Azospirillum brasilense, Azotobacter chroococcum, Lactobacillus acidophillus, Saccharomyces cerevisiae. The combination of macrotunnel production and plastic mulch, along with the application of bacterial consortium 2, yielded the best results in the second year, producing gross and net yields of 25.041 kg ha-1 and 17.330 kg ha-1, respectively. This was associated with the most favorable benefit-cost ratio of 1.41 in the second year.